Assessing Social Work Students On Practicum at the United Arab Emirates University (UAEU): Challenges and Implications. - Abu Sarhan, TAGHREED MAHMOUD; Tedam, Prospera (The Journal of Practice Teaching and Learning, 2021)
Assessing Social Work Students On Practicum at the United Arab Emirates University (UAEU): Challenges and Implications. Dr. Taghreed M. Abu Sarhan¹ (Director of Field Education) Dr Prospera Tedam Social Wellbeing Dept. UAEU Contact: abusarhan@uaeu.ac.ae Abstract The Social Work program at the United Arab Emirates University (UAEU) is the first and the only program-training students for Masters in Social Work (MSW) in the United Arab Emirates. MSW students are required to undertake 500 hours of practice in the field MSW while Bachelor in Social Work (BSW) students are required to complete 400 hours of practicum. This paper outlines both BSW and MSW practicum courses and examines the assessment tools and methods that contribute to their readiness for practice upon qualifying. The authors explore the framework in practicum settings in the UAE and critically reflect on the challenges of the current assessment methods in preparing professional social workers for practice upon graduation. The absence of service user contribution in the assessment process is considered a major disadvantage to the holistic development of social workers in the UAE and will be examined. Significantly, the two authors who are both female address the issue of gender within the context of assessment due to gender segregation in field practicum linked to the cultural and religious requirements in the UAE. The paper concludes with a number of recommendations to improve the assessment of social work students at both BSW and MSW levels at the United Arab Emirates University. Keywords: Social Work, Practicum, UAEU, Assessment methods, BSW and MSW.